Neighbours of cancer-related proteins have key influence on pathogenesis and could increase the drug target space for anticancer therapies - Dezső Módos; Krishna C. Bulusu; Dávid Fazekas; János Kubisch; Johanne Brooks; István Marczell; Péter M. Szabó; Tibor Vellai; Péter Csermely; Katalin Lenti; Andreas Bender; Tamás Korcsmáros (npj Systems Biology and Applications, 2017)
Cancer: Key proteins hiding in the neighbourhood Cancer is considered a systems disease in which the interactors of cancer-related proteins have a key role, also as targets to fight cancer. New therapeutic approaches are needed to improve success rates and to identify suitable proteins as novel, alternative drug targets. We designed a computational approach, combining mutation and differential expression data with network information, to analyse the interactions of cancer-related proteins in colon, breast, liver and lung cancer. We found that first (direct) neighbours, not linked previously to the given cancer type, are similarly important as mutated proteins known to be involved in cancer development. We found 223 drugs already in the clinic targeting these proteins but not yet used against cancer as their oncology relevance was hidden so far. Our observations open up new strategies for target selection and anti-cancer drug discovery.